2020
DOI: 10.1002/ajmg.a.61906
|View full text |Cite
|
Sign up to set email alerts
|

Parenting a child with Marfan syndrome: Distress and everyday problems

Abstract: Marfan syndrome (MFS) is a multisystemic, autosomal dominant connective tissue disorder that occurs de novo in 25%. In many families, parent and child(ren) are affected, which may increase distress in parents. To assess distress, 42 mothers (29% MFS) and 25 fathers (60% MFS) of 43 affected children, completed the validated screening‐questionnaire Distress thermometer for parents of a chronically ill child, including questions on overall distress (score 0–10; ≥4 denoting “clinical distress”) and everyday proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In previous qualitative semi-structured interview studies, parents of children with MFS (4-12 years) and adolescents with MFS (12-18 years) experienced problems of physical functioning, participation in activities and daily life and keeping up with peers [9,10]. Furthermore, studies in children with MFS and hEDS have reported fatigue and pain to negatively impact daily (physical) functioning [7,[11][12][13][14][15][16][17][18][19], a high incidence of pain-related disability [17] and deteriorating physical functioning over time [20]. To our best knowledge, no quantitative studies, using validated questionnaires, have been conducted into pain, fatigue and disability in children with MFS, LDS and molecularly confirmed types of EDS (hereafter EDS).…”
Section: Introductionmentioning
confidence: 99%
“…In previous qualitative semi-structured interview studies, parents of children with MFS (4-12 years) and adolescents with MFS (12-18 years) experienced problems of physical functioning, participation in activities and daily life and keeping up with peers [9,10]. Furthermore, studies in children with MFS and hEDS have reported fatigue and pain to negatively impact daily (physical) functioning [7,[11][12][13][14][15][16][17][18][19], a high incidence of pain-related disability [17] and deteriorating physical functioning over time [20]. To our best knowledge, no quantitative studies, using validated questionnaires, have been conducted into pain, fatigue and disability in children with MFS, LDS and molecularly confirmed types of EDS (hereafter EDS).…”
Section: Introductionmentioning
confidence: 99%
“…The level of cardiac surveillance of the diagnosed Marfan women during pregnancy in Denmark seemed appropriate. It is even likely that some women with MFS, perhaps unnecessarily when scrutinizing the present data, refrain from becoming pregnant, or choose abortion, due to over careful guidance from the clinical and cardiac MFS centers or due to the prospect of having a child with MFS (Minsart et al, 2018; Warnink‐Kavelaars et al, 2020). However, we do not have detailed information concerning the clinical status of the women with diagnosed MFS who chose not to become pregnant, and it may therefore be possible that some of these individuals that decided not to become pregnant, indeed were very high risk patients (Sayama et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Because of the heritable nature of HCTD, parents and children of one family may be diagnosed with (the same) HCTD. Parental HCTD‐related experiences of their own childhood may enable these parents to appreciate problems of their children (Warnink‐Kavelaars, de Koning, et al, 2021; Warnink‐Kavelaars, Beelen, Dekker, et al, 2019; Warnink‐Kavelaars, Beelen, Goedhart, et al, 2019; Warnink‐Kavelaars, van Oers, et al, 2021). It is of additional value to include the perspectives of both parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, parents and children with HCTD, MFS (male and female), and hEDS report in around one of the five cases “somewhat worse to worse” change in health over the last year. These results may be explained by the developing physical features, such as pain of children with HCTD (Castori et al, 2017; Loeys et al, 2010; Loeys & Dietz, 1993; MacCarrick et al, 2014; Malfait et al, 2017; Meester et al, 2017; Van Laer et al, 2014; Warnink‐Kavelaars, de Koning, et al, 2021; Warnink‐Kavelaars, van Oers, et al, 2021). Other studies also reported increased pain of children with HCTD, which negatively influenced activities and participation in daily life (Mu et al, 2019; van Meulenbroek, Conijn, et al, 2020; van Meulenbroek, Huijnen, et al, 2020; Warnink‐Kavelaars et al, 2021; Warnink‐Kavelaars, van Oers, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation